“Freeze-out merger” and cash payment in Peru: Analysis from the provisions of the laws of Delaware - Frías, José Enrique (IUS ET VERITAS, 2016)
The following article deals with the corporate merger agreements where the controlling shareholders of a company legally force the minority group to sell their shares in exchange for compensation. Thus, it seeks to describe, analyze and understand the characteristics, conditions, requirements and motives of FOMs, in order to assess the possibility of introducing such a fusion in Peru, considering our legal context.